1995
DOI: 10.1182/blood.v86.2.491.bloodjournal862491
|View full text |Cite
|
Sign up to set email alerts
|

Expression of retroviral vectors containing the human multidrug resistance 1 cDNA in hematopoietic cells of transplanted mice

Abstract: Transfer of the human multidrug resistance 1 (MDR1) gene to hematopoietic stem cells offers an approach to overcome the myelosuppression caused by a number of antineoplastic drugs. This study was designed to determine the effect of MDR1 gene transfer on overall P- glycoprotein (P-gp) expression in murine hematopoietic cells. Mice were transplanted with bone marrow cells infected with either of two different MDR1 retroviral vectors. A reverse-transcriptase polymerase chain reaction-based assay was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…As a consequence of these studies, expression of ABC transporters to protect against multiple drugs has been actively pursued. Methods for optimizing gene transfer and expression of a splice-corrected MDR1 vector [42] led to high-level expression of the human P-gp in murine stem cells. It was first reported by Bunting et al that Harvey murine sarcoma virus (Ha)MDR1-transduced BM cells showed a significant engraftment advantage relative to those BM cells transduced with a dihydrofolate reductase (DHFR) mutant containing a leucine to tyrosine mutation at codon 22 (HaDHFR L22Y ) [43].…”
Section: Functional Characterization Of Abc Transporters By Overexprementioning
confidence: 99%
“…As a consequence of these studies, expression of ABC transporters to protect against multiple drugs has been actively pursued. Methods for optimizing gene transfer and expression of a splice-corrected MDR1 vector [42] led to high-level expression of the human P-gp in murine stem cells. It was first reported by Bunting et al that Harvey murine sarcoma virus (Ha)MDR1-transduced BM cells showed a significant engraftment advantage relative to those BM cells transduced with a dihydrofolate reductase (DHFR) mutant containing a leucine to tyrosine mutation at codon 22 (HaDHFR L22Y ) [43].…”
Section: Functional Characterization Of Abc Transporters By Overexprementioning
confidence: 99%
“…ABCB1 is also expressed in primitive stem cells, including human CD34 stem cells [4] and c-kit+ cells [5], which can be identified by their ability to transport fluorescent dyes that are ABCB1 substrates, such as rhodamine 123 (Rh123) [6][7][8] and Hoechst 33342 [9][10][11]. One way to purify these stem cells is based on Hoechst dye staining of bone marrow cells to identify a minor fraction of Ôside-populationÕ (SP) cells; this population shows a high repopulating activity and ABCG2 expression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is also not certain which vector will provide optimal expression of DHFR in early myeloid cells. We chose the Harvey vector based on data showing significant mRNA expression in primitive murine myeloid cells [28]. The recent description of retroviral vectors isolated for high level expression in stem cells [29-311 may offer even greater levels of stem cell expression and selection.…”
Section: Discussionmentioning
confidence: 99%